Methodological considerations on land inequaliy - CLACSO, Consejo Latinoamericano de Ciencias Sociales; Luiselli, Cassio; Vargas, Delfino (International Land Coalition, 2021)
This study presents an original methodological proposal for measuring land inequality. It is based on two related observations. First, we emphasise that it is not enough to use a single measure, such as land ownership (as is often the case in existing literature and global databases), to capture the complexity of land inequality. For a more accurate measure, a number of indicators need to be incorporated to enable an assessment of the multidimensional nature of this phenomenon. Second, we underscore that land inequality cannot be measured by the Gini coefficient methodology alone, as this allows only for single variable assessments, besides other challenges. It is for these reasons that we propose the development of a multidimensional land inequality index, based on a series of indicators, through which the relevance of the indicators selected is analysed and countries are grouped using confirmatory factor analysis (CFA) and latent class analysis (LCA).